Dating painting events through by-products of ochre processing: Borologa 1 Rockshelter, Kimberley, Australia. Issue 1 (2nd January 2019) - David, Bruno; Delannoy, Jean-Jacques; Petchey, Fiona; Gunn, Robert; Huntley, Jillian; Veth, Peter; Genuite, Kim; Skelly, Robert J.; Mialanes, Jerome; Harper, Sam; Ouzman, Sven; ,; et al.
Abstract: The 'direct' dating of rock art has proliferated since the development of accelerator mass spectrometry radiocarbon, uranium-series and optically stimulated luminescence dating, yet still, most rock art is not directly datable due to the mineral nature of the constituent pigments. Here we present another method: the recovery and dating by stratigraphic association of small buried fragments of ochre and dried paint drops deposited onto soft sediment surfaces as by-products of paint production and use. These finds also give added contextual occupational information for archaeology of painting events. The case is made through the example of Borologa 1, a richly decorated Wanjina rockshelter in the Kimberley region of northwestern Australia that contains buried hearths, grindstones, earth pigments and small fallen spalls of rock containing traces of pigment and paint drops. Results from excavation indicate the beginning of Wanjina motifs and associated painting conventions on Art Panel B1 sometime between 2, 080–1, 160 cal BP and their proliferation in the past millennium.